Effect of Sulfur and Magnesium Fertilization and Their Interaction on Some Vegetative, Productive, and Quality Traits of Sunflower (Helianthus annuus L.) under Karbala Governorate Conditions - Al-Rubaie, Sanaa Khadem Abdulameer (American Journal of Botany and Bioengineering, 2025)
The experiment was conducted in Karbala Governorate/Al-Husayniyah District during the autumn growing season of 2024 to study the effect of magnesium levels (0, 15, 30, and 45 kg MgO ha⁻¹) and sulfur levels (0, 400, 800, and 1600 kg S ha⁻¹) on the growth and productivity of the Kuban sunflower cultivar. The study was conducted using a randomized complete block design (RCBD) with three replications. The results showed that both magnesium and sulfur had a significant effect on the studied traits. The average plant height increased from 183.53 cm when magnesium was not added to 197.32 cm at 45 kg MgO⁻¹, and also increased with increasing sulfur from 183.88 cm to 196.68 cm. The highest plant height (205.00 cm) was observed at the intersection of the highest magnesium and sulfur levels. Regarding the dry weight of the vegetative parts, it increased from 34.08 g plant⁻¹ to 43.75 g plant⁻¹ with increasing magnesium, and from 35.13 to 42.63 g plant⁻¹ with increasing sulfur. The highest dry weight (50 g plant⁻¹) was recorded with the 45 Mg × 1600 S interaction. Similarly, the weight of 300 seeds increased from 21.29 to 23.40 g with magnesium, and from 21.46 to 23.16 g with sulfur, with the highest weight (25.29 g) recorded with the interaction. Grain yield increased from 5.261 t/h¹ with no addition to 6.495 t/h¹ with magnesium, and from 5.401 to 6.253 t/h¹ with sulfur, reaching a maximum of 7.681 t/h¹ with the combined treatment. Biological yield also gradually increased to 20.287 t/h¹ with the combined treatment, compared to a minimum value of 12.748 t/h¹ with the control treatment. Protein concentration improved from 19.25% to 23.25%, and oil content increased from 41.15% to 46.70% with each element. The highest protein and oil concentrations (28.00% and 52.00%, respectively) were reached at the intersection of the highest magnesium and sulfur levels, indicating a synergistic effect that promotes vegetative growth and protein and oil accumulation in the seeds.